Successful treatment of maternal listeria monocytogenes bacteremia in the first trimester of pregnancy: A case report and literature review - Lai-Man Chan; Ho-Hsiung Lin; Sheng-Mou Hsiao (Elsevier, 2018)
Objective: To report detailed clinical history and management of maternal listeria infection in the first trimester. Case report: A 34-year-old woman at 11 gestational weeks was infected by Listeria monocytogenes with clinical symptoms of acute onset of a fever with subsequent headache and neck stiffness, and was treated with intravenous ampicillin at 2 g every 4 h for 3 weeks. A healthy, unaffected male baby was delivered at term. Histopathologic examination of the placenta did not reveal any chorioamnionitis, granulomas, microabscesses or vasculitis. The neonate developed well without any neurologic compromise at a six-week postnatal follow-up visit. Conclusion: A favorable outcome of maternal listeria infection in the first trimester may be anticipated. Besides, intravenous ampicillin with or without gentamicin should be a reasonable treatment option for maternal listeria infection in the first trimester.